THE EFFECTIVENESS OF REQUESTS FOR MOVING ARRIVALS TO SERVICES VIA ONLINE POPULATION AND CIVIL REGISTRATION ADMINISTRATION (PLAVON DUKCAPIL) SIDOARJO REGENCY - Nuriyah, Rizky Sinta; Mursyidah, Lailul (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to examine the effectiveness of the PLAVON DUKCAPIL online service in managing relocation applications in Sidoarjo Regency, with a focus on improving efficiency, accessibility, and transparency in population administration. Method: The research employed a qualitative descriptive approach, using Richard M. Steers’ effectiveness model, which emphasizes goal achievement, integration, and adaptation. Data were collected through observations, interviews, and documentation to capture perspectives from service providers and users. Results: The findings reveal that PLAVON has been relatively effective in accelerating service processes and reducing physical queues, thereby enhancing public access to population administration services. Nonetheless, several challenges remain, including limited infrastructure, high application volume, low levels of digital literacy, incomplete system integration, and unstable internet connectivity, all of which hinder optimal service delivery. To address these issues, the Department of Population and Civil Registration (Disdukcapil) has conducted routine evaluations and collaborated with universities to strengthen implementation. Novelty: This study contributes by applying Steers’ organizational effectiveness model to assess digital population administration services at the regional level, providing new insights into how structural, technological, and human factors intersect to influence the success of e-government innovations.